IMPLIKASI KEGIATAN USAHA PENITIPAN DENGAN PENGELOLAAN (TRUST) DALAM AKTIVITAS PERBANKAN TERHADAP PEMBAHARUAN HUKUM PERDATA INDONESIA - Tri Handayani; Lastuti Abubakar (JURNAL LITIGASI (e-Journal), 2014)
The issuance of Bank Indonesia Regulation No. 14/7/PBI/2012 regarding Trust add more types of agreements in banking practice. From the legal view, the concept of trust is still debatable, given the concept of trust derived from the Anglo-Saxon legal system that recognize dual -ownership. This concept is not recognize in the legal system agreements in Indonesia, but the existence of the trust agreement is possible based on the principle of freedom of contract in contract law. In practical terms, the use of the concept of trust will intersect with the interests of a third party. Some legal issues have been research in this study are how the Trust agreement under the Indonesia Law of contract; how Bank responsibility as Trustee's for any losses, and how the implications of the Trust against renewal Civil Law. This study utilizes a descriptive analysis, using normative juridical approach. We have conclusion such as: Trust is an agreement that was developed in banking practice based on open systems and the principle of freedom of contract which adopted from Law of contract Based on the agreement, Banks as a trustee shall be liable for losses that incurred caused by Bank negligence in carrying out its functions. Given the concept of custody had unrecognized dual ownership in the Indonesian legal system; hence it is necessary to reform the civil law to accommodate trust activity. Keywords: Trust; dual-ownership; civil law.